1996
DOI: 10.1007/bf02524643
|View full text |Cite
|
Sign up to set email alerts
|

A cereal centromeric sequence

Abstract: We report the identification of a family of sequences located by in situ hybridisation to the centromeres of all the Triticeae chromosomes studied, including the supernumerary and midget chromosomes, the centromeres of all maize chromosomes and the heterochromatic regions of rice chromosomes. This family of sequences (CCS1), together with the cereal genome alignments, will allow the evolution of the cereal centromeres and their sites to be studied. The family of sequences also shows homology to the CENP-B box.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(67 citation statements)
references
References 28 publications
2
65
0
Order By: Relevance
“…These tandemly repeated sequences evolve rapidly and tend to be conserved only in closely related species . A second type of sequence, represented by RCS1, RCH1, RCH2 and RCH3 is a low to middle-copy, interspersed sequence that may be conserved across many genera (Aragon-Alcaide et al 1996;Jiang et al 1996;Dong et al 1998;Miller et al 1998;Cheng et al 2002). RCS1 was present at the centromeres of Z. palustris, whereas the highly repetitive RCS2/CentO sequence was not present in Z. palustris, even under lowstringency Southern conditions (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…These tandemly repeated sequences evolve rapidly and tend to be conserved only in closely related species . A second type of sequence, represented by RCS1, RCH1, RCH2 and RCH3 is a low to middle-copy, interspersed sequence that may be conserved across many genera (Aragon-Alcaide et al 1996;Jiang et al 1996;Dong et al 1998;Miller et al 1998;Cheng et al 2002). RCS1 was present at the centromeres of Z. palustris, whereas the highly repetitive RCS2/CentO sequence was not present in Z. palustris, even under lowstringency Southern conditions (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the sequences known as centromere-specific repetitive elements, RCS1 (Aragon- Alcaide et al 1996;Dong et al 1998), RCH1, RCH2 and RCH3 , were homologous to a portion of the internal sequences of RIRE7 (Kumekawa et al 2001). We further investigated the distribution mode of LTRs and gag-pol sequences of other rice retrotransposons, RIRE2 (Ohtsubo et al 1999), RIRE3 (Kumekawa et al 1999), RIRE7 (Kumekawa et al 2001) and RIRE8 (Kumekawa et al 1999).…”
Section: Multiple Repetitive Elements Lie In Cen5mentioning
confidence: 99%
“…Aragon-Alcaide et al (1996) and Jiang et al (1996) first reported the CCS1 family repeats and pSau3A9 repeats commonly found in most of…”
Section: Introductionmentioning
confidence: 99%
“…CENP-B proteins are also found in plants ( Barbosa-Cisneros and HerreraEsparza, 2002), suggesting either that the capture of this retroelement gene predates the plant-animal divergence or, possibly, that capture of this or a similar retroelement gene has occurred multiple times. The CRR and CRM retroelement families of rice and maize, respectively, may represent a more indirect case of transposon adoption (Aragon-Alcaide et al, 1996;Jiang et al, 1996;Ananiev et al, 1998;Miller et al, 1998;Presting et al, 1998). These elements are specifically targeted to centromeres, and show significant sequence conservation among their LTRs, even between species, which may signal that the sequences are under selective pressure and that they predate the divergence of rice and maize (Zhong et al, 2002;Sharma and Presting, 2008).…”
Section: Co-option Of a Te Gene By The Hostmentioning
confidence: 99%